2018
DOI: 10.1530/eje-18-0478
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of glucose levels in pregnancy: genetic risk scores analysis and GWAS in the Norwegian STORK cohort

Abstract: ObjectiveHyperglycaemia during pregnancy increases the risk of adverse health outcomes in mother and child, but the genetic aetiology is scarcely studied. Our aims were to (1) assess the overlapping genetic aetiology between the pregnant and non-pregnant population and (2) assess the importance of genome-wide polygenic contributions to glucose traits during pregnancy, by exploring whether genetic risk scores (GRSs) for fasting glucose (FG), 2-h glucose (2hG), type 2 diabetes (T2D) and BMI in non-pregnant indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…So far, only two of the identified placental miR-eQTLs have been reported in the GWAS catalog: rs10853101 (miR-10a-5p) associated with the risk to diverticular disease and rs1424569 (hsa-miR-490-3p) with cardiac PR interval. In perspective, the phenotype effects of placental miR-eQTLs individually or as a component in polygenic risk scores for pregnancy-related traits ( Moen et al, 2018 ; Ursini et al, 2018 ; Lamri et al, 2020 ; Steinthorsdottir et al, 2020 ) are still to be clarified. The pilot association testing of miR-eQTLs with newborn traits in the current study may have suffered from inadequate statistical power due to highly polygenic contribution (each variant with small effect), as well as combined effect of maternal and fetal genetics in modulating anthropometric parameters at birth ( Beaumont et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, only two of the identified placental miR-eQTLs have been reported in the GWAS catalog: rs10853101 (miR-10a-5p) associated with the risk to diverticular disease and rs1424569 (hsa-miR-490-3p) with cardiac PR interval. In perspective, the phenotype effects of placental miR-eQTLs individually or as a component in polygenic risk scores for pregnancy-related traits ( Moen et al, 2018 ; Ursini et al, 2018 ; Lamri et al, 2020 ; Steinthorsdottir et al, 2020 ) are still to be clarified. The pilot association testing of miR-eQTLs with newborn traits in the current study may have suffered from inadequate statistical power due to highly polygenic contribution (each variant with small effect), as well as combined effect of maternal and fetal genetics in modulating anthropometric parameters at birth ( Beaumont et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is preliminary evidence to suggest that genetic variants associated with cardiometabolic phenotypes in the general population (i.e. men and women who are not pregnant) are also associated with the same traits in mothers during pregnancy, meaning that SNPs that proxy these traits also proxy the exposures in pregnant women 2 , 31 …”
Section: Using Two-sample Mr Studies To Analyse the Causal Effect Of mentioning
confidence: 99%
“…In a previous study in Gen3G and HAPO-EU, we found that trait-based polygenic scores (with component variants selected on the basis of effects outside pregnancy) for fasting glucose, fasting insulin, insulin secretion, and insulin sensitivity were associated with GDM (4). Similarly, Moen et al (37) found associations between polygenic scores for fasting glucose, BMI, and T2D and glucose levels in pregnancy. The current study builds upon this literature by testing variants grouped by physiologic pathway (rather than by effects on a single trait) for associations with pregnancy glycemic traits and GDM; this allows us to identify physiologic pathways that play a role in GDM pathogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have tested T2D-associated variants for association with GDM, but few have probed variants grouped on the basis of more specific physiology (2,4,(37)(38)(39). In a previous study in Gen3G and HAPO-EU, we found that trait-based polygenic scores (with component variants selected on the basis of effects outside pregnancy) for fasting glucose, fasting insulin, insulin secretion, and insulin sensitivity were associated with GDM (4).…”
Section: Discussionmentioning
confidence: 99%